"Parece que falta um pedaço da gente" : tecendo histórias sobre o desenlace conjugal - Arruda, Débora Pinho (2015)
VIII ABSTRACT In this dissertation , we aim to understand the conflicted marita l disruption in the judicial context of the dispute for children custody. We developed a research with qualitative approach, considering the nature of our object of study, which involves the compre hension of people's experience . As construction strategy of the empirical material we performed life history interviews with twelve subjects who experienced the phenomenon in question, selected from two Family Courts of the Ceará Court of Justice and Family Public Defender, located in th e city Fortaleza. From these people, we have selected a couple who showed in their report explanatory elements about the conflicted marital breakup. To assist the analysis of this reality, we have made use of Paul Ricoeur's Hermeneutic Phenomenology, as we ll as specialized literature on the topic of marital disruption, performing an in - depth analysis of the presented narratives. We observed that the birth and care of a child, hou sework, power relations, family interference in marriage and previous relations hips marks are some of the reasons of marital conflict during the marriage. Th e marital infidelity, jealousy, spouse aggression and the relationship with children from previous relationships were identified as main reasons for marital outcome. The division of the interaction with the children between the parents was constituted as the central cause of post - separation conflicts We observed the experience of mourning with marked distress during the dissolution of a union, which involves a process of transfor mation of the identity of the subjects. One of the main difficulties resulting from this disruption is the differentiation between marital and parental roles: cease to be husband / wife while still being father / mother. We believe that this study may cont ribute to a greater understanding of this phenomenon, to improve the practice of professionals working with the theme, as well as to support the proposition of programs aimed at offering support to families experiencing a marital outcome.